Decision Support System of Keyword Selection Web Site Using Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) - Murdiyanto, Aris Wahyu (Compiler, 2019)
The keyword is one or a group of words used by websites to improve your visibility on search engines. The selection of keywords from the results displayed by Google's keyword planner still not match the expectations of the webmaster, so that needs to be determined the choice and order of priority keywords which will be optimized beforehand. Therefore, a system that supports webmasters in making decisions on choosing keywords that will be optimized previously for search engines is needed. The methods used in this research is Analytical Hierarchy Process (AHP) to find the weighting parameters and Simple Additive Weighting (SAW) applied to find the final value and rank. The results showed that the system is running as expected, so it can be used as a basis in support of the decision of the webmaster in determining the priority of the optimization of keywords that will be worked out with the results of the comparison between the manual system with 100%.